Relationship Between Polyunsaturated Fatty Acids and Psychopathology in the NEURAPRO Clinical Trial - Maximus Berger; Maximus Berger; Barnaby Nelson; Barnaby Nelson; Connie Markulev; Connie Markulev; Hok Pan Yuen; Hok Pan Yuen; Miriam R. Schäfer; Miriam R. Schäfer; Nilufar Mossaheb; Nilufar Mossaheb; et al. (Frontiers in Psychiatry, 2019)
BackgroundDeficiencies in membrane polyunsaturated fatty acids (PUFA) such as omega-3 (n-3) fatty acids are thought to contribute to the pathophysiological processes underlying psychotic disorders. Emerging evidence suggests that the levels of PUFA are related to clinical symptoms but significant heterogeneity exists between studies. Here, we investigated associations of membrane PUFA with clinical symptoms and functioning in a large sample of individuals at ultra-high risk (UHR) for psychosis.MethodsA total of 285 participants of the NEURAPRO clinical trial were investigated for erythrocyte PUFA levels, including the n-3 index, n-6/n-3 PUFA ratio, docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA). Severity of general psychopathology [Brief Psychiatric Rating Scale (BPRS)], psychotic symptoms (BPRS psychosis subscale), negative symptoms [Scale for the Assessment of Negative Symptoms (SANS)], manic symptoms [Young Mania Rating Scale (YMRS)], depressive symptoms [Montgomery Asberg Depression Rating Scale (MADRS)], and functioning [Social and Occupational Functioning Scale (SOFAS), Global Functioning Social (GF-S) and Role (GF-R) scales] were assessed concurrently. Partial correlation taking into account the effects of gender, age, and smoking was used to examine the relationship between PUFAs and symptoms severity. ResultsThe n-3 index negatively correlated with the severity of general psychopathology, psychotic symptoms, depressive symptoms, and manic symptoms. The n-6/n-3 PUFA ratio positively correlated with severity of psychotic and depressive symptoms. The n-3 PUFA DHA negatively correlated with the severity of general psychopathology, positive, manic, and depressive symptoms. EPA negatively correlated with manic symptoms. Nervonic acid, an n-9 monounsaturated fatty acid, positively correlated with general psychopathology, positive and negative symptoms, depressive symptoms, and manic symptoms. The long-chain saturated fatty acid tetracosanoic acid positively correlated with general psychopathology, positive, manic, and depressive symptoms.ConclusionsPartially consistent with a previous study, psychotic symptoms, depressive symptoms, and symptoms of mania were associated with several classes of FAs in the present study. These findings support the relevance of membrane fatty acids for the onset of psychotic symptoms and indicate that FAs should be further evaluated as biomarkers in the UHR for psychosis group.Clinical Trial RegistrationANZCTR, identifier: 12608000475347